Activin A Secreted From Peripheral Nerve Fibroblasts Promotes Proliferation and Migration of Schwann Cells - Li, Yan; Cheng, Zhenghang; Yu, Fanhui; Zhang, Qi; Yu, Shu; Ding, Fei; He, Qianru (Frontiers in Molecular Neuroscience, 2022)
The peripheral nervous system has remarkable regenerative capabilities. Schwann cells (SCs) and fibroblasts are known to play crucial roles in these processes. In this study, we delineated the differential effects of peripheral nerve fibroblasts and cardiac fibroblasts on Schwann cells. We found that peripheral nerve fibroblasts significantly promoted Schwann cell proliferation and migration compared to cardiac fibroblasts. The cytokine array results identified 32 of 67 proteins that were considered differentially expressed in peripheral nerve fibroblasts versus cardiac fibroblasts. Among these, 25 were significantly upregulated in peripheral nerve fibroblasts compared to cardiac fibroblasts. Activin A, the protein with the greatest differential expression, clearly co-localized with fibroblasts in the in vivo sciatic never injury rat model. In vitro experiments proved that activin A secreted from nerve fibroblasts is the key factor responsible for boosting proliferation and migration of SCs through ALK4, ALK5, and ALK7. Overall, these findings suggest that peripheral nerve fibroblasts and cardiac fibroblasts exhibit different patterns of cytokine secretion, activin A secreted from peripheral nerve fibroblasts can promote the proliferation and migration of Schwann cells.